2016
DOI: 10.15835/nbha44210399
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antifungal Effects of <i>Vitex agnus-castus</i> L. and <i>Myrtus communis</i> L. Plants

Abstract: The purpose of this study was to assess the effectiveness of essential plant oils from Vitex agnus-castus L. ), and plant essential oils were applied at concentrations of 0.5, 1, 1.5, 2, 5 and 10 (μL/Petri -1 ) into the 5 mm diameter wells opened on the Petri dish surface. After that, the Petri dishes incubated at 22±2 °C. The results of this study, the essential oil of M. communis, at a dose of 10 μL/ Petri, inhibited the 100% mycelium growth of V. dahliae, S. sclerotiorum and R. solani. The highest dose of V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…In another study, Yilar et al investigated the antifungal effects of vitex extract on some fungi. The tests revealed that this extract had a high range of antifungal effects, such that 5 µl of vitex essential oil reduced 90.23%, 55.68% and 63.35% of the mycelial growth in Verticillium dahlia , Sclerotinia sclerotiorum, and Rhizoctonia solani , respectively [ 19 ]. Asdadi et al evaluated the antifungal effect of vertex seed extract on four Candida species isolated from cases of nosocomial infection.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Yilar et al investigated the antifungal effects of vitex extract on some fungi. The tests revealed that this extract had a high range of antifungal effects, such that 5 µl of vitex essential oil reduced 90.23%, 55.68% and 63.35% of the mycelial growth in Verticillium dahlia , Sclerotinia sclerotiorum, and Rhizoctonia solani , respectively [ 19 ]. Asdadi et al evaluated the antifungal effect of vertex seed extract on four Candida species isolated from cases of nosocomial infection.…”
Section: Discussionmentioning
confidence: 99%
“…Fusarium oxysporum , Rhizoctonia solani , Sclerotinia sclerotiorum and Verticillium dahlia were inhibited significantly by applying the oil of Vitex, which contains eucalyptol (1,8‐cineole) (17·75%) and 8‐caryophyllene (13·21%) as the main compounds (Yilar et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…; Yilar et al . ), that is , Aspergillus apple rot has been reduced significantly by applying of 1,8‐cineole that isolated from V. agnus‐castus essential oil (Stojković et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, 1,8-cineole has been proven to have good antifungal activity against Aspergillus apple rot [21]. V. agnus-castus oil contains the main compounds of 1,8-cineole (eucalyptol) and 8-caryophyllene, which significantly inhibited the growth of F. oxysporum, R. solani, Sclerotinia sclerotiorum, and Verticillium dahlia [68]. Melia azedarach wood-treated with the n-hexane oil of V. agenus-castus leaves at a 1%, 2%, or 3% concentration showed good antifungal activity against F. culmorum, Rhizoctonia solani, and P. chrysogenum [9], where the main compounds were eucalyptol (22.1%), (E)-β-caryophyllene (18.3%), and β-sitosterol (12.4%).…”
Section: Chemical Composition Of the Eosmentioning
confidence: 99%